Effect of seminal plasma on hipoosmotic swelling test in fresh alpaca spermatozoa - Pacheco Curie, Joel I. (2017)
A study was designed with the objective of evaluating the effect of seminal plasma on the response to the hypoosmotic swelling test (HOST) in alpaca spermatozoa, for which three experimental groups were organized as follows: Group 1(n=15) plasma free sperm seminal (obtained from the vas deferens, aspirated in PBS), Group 2(n=15) free seminal plasma sperm reconstituted with seminal plasma (obtained from the vas deferens, aspirated in PBS, mixed in 50/50% with seminal plasma) and Group 3(n=15) whole semen (obtained by artificial vagina), The samples were incubated in a hypoosmotic solution adjusted to 100mOsmol (sodium citrate+fructose+2H2Ocsp 100mL). 0.1mL of semen+0.9mL of hypoosmotic solution was mixed, incubated for 30minutes in a water bath at 37°C and the reaction was stopped with 0.1mL of 4% formaldehyde. A count of at least 200 spermatozoa was performed per sample, using an optical microscope with immersion objective (100X), the vitality was evaluated by supravital eosin staining (0.7%)-nigrosin(1%), the results indicate that it does not exist a detrimental effect of the seminal plasma on the endosmotic response, being, on the contrary, superior in the whole semen; the vitality of the spermatozoa with and without seminal plasma is similar, however it decreases when it is reconstituted with seminal plasma, possibly due to the seminal plasma of another animal; there is no positive correlation between endosmosis and vitality, indicating that the latter would not necessarily reflect the integrity of the membrane, which is why it is recommended to perform this test routinely in alpaca semen exams.